Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1634/stemcells.18-6-422
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of c‐erbB Positive Cells to a Ligand Toxin and Its Utility in Purging Breast Cancer Cells from Peripheral Blood Stem Cell (PBSC) Collections

Abstract: Autografting following high-dose conditioning is being increasingly offered to breast cancer sufferers, without due regard to the reinfusion of malignant cells. We sought to determine if a breast cancer cell line could be successfully purged from peripheral blood stem cell (PBSC) harvests using a ligand-toxin molecule directed to heregulin-activated erbB receptors. Initial experiments demonstrated no reduction in hemopoietic colonyforming ability in the presence of ligand toxin (2 nM). Breast cancer cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…Non-viral-based purging systems In an ex vivo setting, several purging strategies such as, tumour targeting with monoclonal antibodies (MoAbs) and/or linked to toxins 39,40 positive haematopoietic stem AFP mRNA detected in all patients after 1st and 2nd rounds of (IC) but not detected in 3 4 samples after 3rd round of IC Kasahara et al cell (CD34 þ ) selection 41,42 ex vivo chemotherapy, 43 photodynamic purging processes 44,45 and receptor-targeted ligand toxins such as Shiga-like toxin-1, a ribosome-inactivating protein with receptor expression in several tumour cell lines but not in CD34 þ cells 46,47 have been tested to minimize tumour cell contamination in autografts and reduce post transplant relapse. While the efficacy of the latter two purging methods has yet to be tested in clinical trials, the other methods, for a number of reasons have not been universally adopted into the clinical setting for depleting autografts of tumour cells.…”
Section: Ex Vivo Purging Strategiesmentioning
confidence: 99%
“…Non-viral-based purging systems In an ex vivo setting, several purging strategies such as, tumour targeting with monoclonal antibodies (MoAbs) and/or linked to toxins 39,40 positive haematopoietic stem AFP mRNA detected in all patients after 1st and 2nd rounds of (IC) but not detected in 3 4 samples after 3rd round of IC Kasahara et al cell (CD34 þ ) selection 41,42 ex vivo chemotherapy, 43 photodynamic purging processes 44,45 and receptor-targeted ligand toxins such as Shiga-like toxin-1, a ribosome-inactivating protein with receptor expression in several tumour cell lines but not in CD34 þ cells 46,47 have been tested to minimize tumour cell contamination in autografts and reduce post transplant relapse. While the efficacy of the latter two purging methods has yet to be tested in clinical trials, the other methods, for a number of reasons have not been universally adopted into the clinical setting for depleting autografts of tumour cells.…”
Section: Ex Vivo Purging Strategiesmentioning
confidence: 99%
“…Widely cited purging methods of autografts include the use of ex vivo chemotherapy, tumor targeting monoclonal antibodies linked with toxins or selected on immunocolumns, and positive (CD34 ϩ ) selection. 12,13 More recently, photodynamic purging processes, [14][15][16] virus-directed enzyme prodrug therapy, 17 receptor-targeted ligand toxins, 18,19 and attenuated replication-competent virus-based purging techniques 20 have been reported. Yet, to date no method has proved 100% successful in depleting autografts of tumor cells in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…HRG is one of the factors that influence the response of the cells to E2. Overexpression of HRG in MCF-7 cells has been shown to confer E2 independence and antiestrogen resistance (Keir et al, 2000). Furthermore, experimental data in our laboratory have demonstrated that HRG can interfere in the negative crosstalk regulation between erbB2 and the estrogen receptor (ER) (Peles and Yarden, 1993;Alper et al, 2000).…”
Section: Introductionmentioning
confidence: 99%